Thoracic esophageal perforation by the use of Magill forceps in infant, success with non-operative treatment: case report - Abdel-Kémal Bori Bata; Antoine Séraphin Gbénou; Joseph Akodjènou; Aboudou Raïmi Kpossou; Bruno Noukpozoukou; Armand Michel Fiogbe (SpringerOpen, 2021)
Abstract Background Esophageal perforation is a rare surgical pathology in children. Thoracic esophageal perforation is more severe than cervical esophageal perforation. Iatrogenic cause, mainly by endoscopy, is the most common in esophageal perforation. However, perforation induced by "Magill forceps" is exceptional. Case presentation A systematic physical examination revealed pyrexia severe respiratory distress and right-sided pleural effusion. We report the success of non-operative treatment applied to thoracic esophageal perforation due to Magill forceps in a 24-month-old male infant. The immediate and short-term outcomes were excellent. Conclusions Non-operative treatment is possible in iatrogenic perforation of thoracic esophageal in infants. This treatment delivers excellent outcome in carefully selected patients.